Hubungan antara dukungan suami dan motivasi tenaga kesehatan tentang antenatal care dengan frekuensi kunjungan kehamilan - Hendrik Probo Sasongko; Febrika Nanda; Setyo Kurniawan; Sofwatul Mujayadah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Routine antenatal care (ANC) is crucial for the early detection of complications and the improvement of maternal and fetal health. However, the frequency of ANC visits in Indonesia has not yet reached optimal standards. Contributing factors include a lack of husband support and low motivation among health workers in providing education and support services. Purpose: To identify the relationship between husband support and health worker motivation regarding ANC and the frequency of ANC visits within the